Multi-bandwidth data path design for 5G wireless mobile internets - Gani, Abdullah; Li, X.; Yang, L.; Zakaria, O.; Anuar, N.B. (2009)
The 5th generation is envisaged to be a complete network for wireless mobile internet, which has the capability to offer services for accommodating the application potential requirements without suffering the quality. The ultimate goal of 5G is to design a real wireless world, that is free from obstacles of the earlier generations. This requires an integration of networks. In this paper, we propose the design of Multi-Bandwidth Data Path by integrating the current and future networks for new network architecture of 5G real wireless world. We also present our proposed architecture and results of the simulation.